Applications of rare event dynamics on the free energy calculations for membrane protein systems - Wang, Yun-Kun; Wei, Dong-Qing; Gu, Ruo-Xu; Fan, Huai-Meng; Ulmschneider, Jakob (Canadian journal of chemistry, 2013)
Techniques of rare event dynamics were reviewed, including string methods, which will be implemented with the biochemical simulation packages. The existing methods were applied to study biological systems with relevance to drug design and drug metabolism. The rare event dynamics simulations were performed to understand the kinetic and thermodynamic free energy information on the drug binding sites in the M2 proton channel, the free energy of insertion and association of membrane proteins and membrane active peptides. Results give a theoretical framework to interpret and reconcile existing and often conflicting opinions.